Clinical Trial Portfolios: A Critical Oversight in Human Research Ethics, Drug Regulation, and Policy - London, Alex John (The Hastings Center report, 2019)
Regulators rely on clinical trials for drug approval and labeling decisions. Health systems and clinicians rely on the evidence from trials to determine treatment, and patients rely on it to decide which courses of care to undertake. Many of these stakeholders presume that the careful review of individual studies is enough to address the ethical and scientific questions that arise in clinical trials. In what follows, however, we demonstrate that explicit consideration of trial portfolios—series of trials that are interrelated by a common set of objectives—is crucial. the ethical acceptability and evidentiary probity of individual trials can change depending on the characteristics of the portfolios in which they are embedded. Second, how trial portfolios are composed, how well they are coordinated, and how efficiently they use information determines the balance of risks and benefits they present as well as their different prospects for generating socially valuable information; these three factors also raise distinct questions of justice.